Electroacupuncture ameliorates inflammatory response induced by retinal ischemia-reperfusion injury and protects the retina through the DOR-BDNF/Trkb pathway - Guo, Runjie; Zhang, Yongjie; Geng, Yue; Chen, Ping; Fu, Tiantian; Xia, Yong; Zhang, Ren; Zhu, Yuan; Jin, Jingling; Jin, Nange; Xu, Hong; Tian, Xuesong (Frontiers in Neuroanatomy, 2023)
Objectives: Retinal ischemia-reperfusion injury (RIRI) is the common pathological basis of many ophthalmic diseases in the later stages and inflammation is the main damage mechanism of RIRI. Our study aimed to assess whether electroacupuncture (EA) has a protective effect against RIRI and to elucidate its related mechanisms. Methods: A high-intraocular pressure (HIOP) model was used to simulate RIRI in Wistar rats. The pathological changes in the retina were observed by H&E staining after HIOP. TUNEL staining was utilized to observe retinal cell apoptosis. The mRNA expression of IL1-β, TNF-α, IL-4, IL-10, δ-opioid receptor (DOR), brain-derived neurotrophic factor (BDNF) and tropomyosin-related kinase B (TrkB) in the retina was measured by quantitative real-time PCR. Results: HIOP caused structural disorders of the retina, decreases in RGCs and increases in retinal cell apoptosis. At 1 and 3 days of RIRI, retinal apoptotic cells in the EA group were significantly reduced, while there was no distinct difference in the EA group compared with the HIOP group at 7 days of RIRI. Compared with that in the HIOP group, the expression of DOR and TrkB was increased, the expression of anti-inflammatory factors was increased, and the expression of pro-inflammatory factors was decreased in the EA group. Conclusion: Our study identify that EA at Jingming (BL1) and Shuigou (GV26) or at Jingming (BL1) and Hegu (LI4) can inhibit RIPI induced inflammation through activating the DOR-BDNF/TrkB pathway to protect the retina, especially the pair of Jingming (BL1) and Shuigou (GV26) has better inhibitory effects on inflammation.